1994
DOI: 10.1042/bj2970069
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthesis from glucose and ammonium chloride by guinea-pig kidney tubules

Abstract: 1. At a physiological concentration (5 mM), glucose was found to be metabolized by isolated kidney cortex tubules prepared from fed guinea pigs. 2. The release of 14CO2 from [U-14C]glucose indicated that oxidation of the glucose carbon skeleton represented about 50% of the glucose removed; significant amounts of lactate and glutamine also accumulated. 3. Addition of 0.1-10 mM NH4Cl led to a dose-dependent stimulation of glucose metabolism which was accompanied by a large increase in lactate and glutamine accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In addition to its traditional role, muscle tissue has other functions, such as a role in immunology. The amino acid glutamine is synthesized from glucose in the skeletal muscle [8, 9]. Continuous maintenance of a sufficient glutamine concentration in the blood is necessary for the proper functioning of the immune system and survival [10].…”
Section: Why Insulin‐dependent and ‐Independent Transporters?mentioning
confidence: 99%
“…In addition to its traditional role, muscle tissue has other functions, such as a role in immunology. The amino acid glutamine is synthesized from glucose in the skeletal muscle [8, 9]. Continuous maintenance of a sufficient glutamine concentration in the blood is necessary for the proper functioning of the immune system and survival [10].…”
Section: Why Insulin‐dependent and ‐Independent Transporters?mentioning
confidence: 99%
“…Finally, the high glutamine synthetase activity, found in rabbit kidney nephrons ( Chauvin et al, 1997 ), has been shown to trap ammonia as glutamine, thus rendering it unavailable for release into both the urine and the systemic circulation via the renal vein. Furthermore, glutamine synthetase activity in herbivorous kidneys has been shown to be increased following the administration of ammonium chloride ( Michoudet et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose contributes particularly for the production of alanine by providing its carbon skeleton[3]. There is also evidence suggesting that glucose may also provide carbon skeleton for glutamine[3–6]. This–together with the insulin‐stimulated uptake of some amino acids–leads to a net protein synthesis in the muscle during hyperinsulinaemia[7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Because large amounts of proteins are synthesized and degraded daily[9], it is difficult to perceive the contribution of glucose‐derived amino acids to the amino acid pool during hyperinsulinaemia. However, there is a net release of alanine and glutamine from the muscle due to the conversion of glucose to alanine and possibly also to glutamine[4–6,10]. Alanine can be used for gluconeogenesis in the liver[11].…”
Section: Introductionmentioning
confidence: 99%